Time-resolved spectroscopic studies of reactive intermediates - Murphy, Thomas S. (2016)
Chapter 1. Introduction. An introduction to the detection of reactive intermediates by various spectroscopic techniques is given, as well as a brief introduction to perfluorinated solvents, which are used throughout the work presented in Chapters 2 to 4. Chapter 2. Time-Resolved Studies of Spin-Forbidden Reactions of Transition Metal Carbonyls with Weak Ligands. The photolysis of a series of first-row transition metal carbonyl compounds which have been previously reported to form 16-electron coordinatively unsaturated intermediates was examined in a series of perfluorinated solvents using TRMPS (time-resolved multiple probe spectroscopy) and TRIR (time-resolved infrared) spectroscopy. In the case of Fe(CO)5, CpMn(CO)3, (MeCp)Mn(CO)3 and CpV(CO)4, the rate of reaction of the 16-electron intermediate with the perfluorinated solvent was found to be slower than that previously reported for weakly coordinating solvents (e.g. alkanes). Addition of cyclopentane, CO2, Xe and C2H6 to a solution of CpMn(CO)3 in perfluoro(methylcyclohexane) was shown to change the rate of this spin-forbidden reaction, as well as the (CO) band positions of the resulting 1CpMn(CO)2X (X = solvent or dopant) complex. Other perfluorinated materials (perfluoro(hexanes) and perfluoro(triethylamine)) are also shown to allow formation of such weakly-coordinated alkane and noble gas complexes in room-temperature liquid solution. Chapter 3. Further Time-Resolved Studies of Alkane and Noble Gas Complexes in Room Temperature Perfluoroalkane Solutions.The photochemistry of various model transition metal compounds in perfluoroalkane solutions was examined with TRMPS and TRIR spectroscopy. 266 nm photolysis of CpRe(CO)3, Cp*Re(CO)3 and CpRe(CO)2(N2) in perfluoro(methylcyclohexane) solution was found to result in the formation of two distinct dicarbonyl species of the form CpRe(CO)2X, the first of which decay completely on the nanosecond timescale to form the second. The rate of formation, rate of decay and (CO) band positions of this second dicarbonyl species were found to be dependent on the nature of the the solvents or dopants including Xe or cyclopentane present in solution. Similar results were observed for complexes of the form M(CO)6 (M = Cr, Mo, W). DFT calculations were used in conjunction with spectroscopic studies to attempt to confirm the structure of the initially formed species following photolysis of CpRe(CO)3 and M(CO)6 in PFMCH solution. Good agreement was observed between the calculated (CO) band positions of coordinatively unsaturated species and the unknown initially formed CO loss species. Doping of CH4 or C2H6 into a solution of CpRe(CO)3 or Cp*Re(CO)3 resulted in observation of a C-H activated alkyl hydride complex, with the amount of observed C-H activation vaying in the order: CpRe(CO)3 with ethane < Cp*Re(CO)3 with ethane < CpRe(CO)3 with methane < Cp*Re(CO)3 with methane. Photolysis of CpRh(CO)2 in perfluoroalkane solvents was shown to lead to formation of a monocarbonyl solvent complex, followed by the dimeric species Cp2Rh2(CO)3, as well as another species, very tentatively assigned to a C-F activated oxidative addition product. Addition of Xe to the above solution was shown to slow formation of the dimeric species, with no evidence of C-F activation observed, indicating formation of CpRh(CO)Xe in room temperature solution. Chapter 4. Time-Resolved Spectroscopic Studies of Organometallic Triethylsilane Complexes. TRMPS studies of CpMn(CO)3, CpRe(CO)3 and Cp*Re(CO)3 were undertaken in neat HSiEt3 solvent. Photolysis of CpMn(CO)3 resulted in initial formation of 3CpMn(CO)2, following by both direct and indirect formation of the Si-H activated speciesin both cases. Photolysis ofW(CO)6 was found to result in initial formation of the ethyl-boundW(CO)5(EtSiHEt2), which interconverted to form the Si-H-bound speciesW(CO)5(H−SiEt3). Preliminary time-resolved x-ray absorption fine structure spectroscopic studies are also presented. Photolysis of W(CO)6 and CpRe(CO)3 in neat HSiEt3 was observed to cause subtle changes in the absorption edge compared to ground state XAFS spectra, indicating possible formation of transient species in both cases. Chapter 5. Experimental. The experimental techniques utilised in this Thesis are described.